Determination of phthalate esters in teas and tea infusions by gas chromatography–mass spectrometry. (15th April 2016) - Du, Liping; Ma, Lijuan; Qiao, Yang; Lu, Yan; Xiao, Dongguang
Highlights: SDE-GC–MS was applied for quantitative determination of the five PAEs in teas and tea infusions. The proposed method afforded a wide range of linearity and high linear regression coefficients with good limit detection. Dissolving ratios of the five PAEs were calculated. Safety evaluation demonstrated no risk to human health of the selected tea samples with the population drinking habit. Abstract: Phthalate esters (PAEs), a group of environmental pollutants which are carcinogenic to human body, have been detected in teas. In this work, five PAEs in teas and tea infusions were quantitatively determined by a modified simultaneous distillation extraction (SDE) coupled with gas chromatography–mass spectrometry. After the optimization of SDE, the proposed method afforded a wide range of linearity and high linear regression coefficients with the limits of detection range of 0.24–3.72 μg/kg. The average recoveries were 79.83–116.67% for tea samples and 78.22–101.64% for tea infusions with all the relative standard deviations below 20%. The total content of five PAEs in teas was 1.135–3.734 mg/kg and the total dissolving ratio of five PAEs from tea to infusion was 19.05–28.07% for the selected tea samples. The risk assessment result of all the selected tea samples demonstrated that the population with the habit of drinking tea won't cause risk to human health.